Effects of Controlling of Blood Glucose in Adult Non-Diabetic Patients Undergoing Mitral Valve Replacement (Anwer Khan Modern Medical College Journal, 2019)
Background: The objective of this study was to see whether there is an association between high blood glucose levels after operation under CPB and post-operative morbidity and mortality. Methodology: This cohort study was carried out in the Department of Cardiac Surgery at National Institute of Cardiovascular Disease (NICVD), Sher-e-Bangla Nagar, Dhaka from January, 2012 to December, 2013 for a period of twenty four (24) months. A total number of 110 patients who underwent MVR operation with CPB were enrolled in this study as per inclusion and exclusion criteria. Patients were divided into two groups according to their blood glucose levels, recorded within first 60 hrs after Mitral Valve Replacement Surgery under Cardiopulmonay Bypass. Patients having blood glucose level of less than 10.1 mmol/L (unexposed) and patients having blood lactate level of 10.1 mmol/L or more (exposed) were grouped. Post operative variables were observed and recorded during the hospital course of the patient. Result: A total number of 110 patients were enrolled in this study. Blood glucose levels lower than or equal to10 mmol/L after MVR were present in 55(50%) patients (Group A) Blood glucose levels higher than 10 mmol/L after MVR were present in 55(50%) patients. Postoperative morbidity was higher in this group (Group B) than in the patients who had peak blood glucose levels of less than or equal to 10 mmol/L MVR (p=0.001). Postoperative ICU stay was prolonged in patients with elevated levels of blood glucose after MVR under CPB compared with of patients with lower blood glucose levels (p=0.001). Other common morbidities are Neurological complication (p=0.04), Renal dysfunction (p=0.01), wound infection (p=0.04), Post-operative hospital stay (p=0.004). also higher in group B patient, as well as mortality (p=0.31). Conclusions: Blood glucose concentration of 10.1 mmol/L or higher after MVR under CPB is an important issues related to postoperative morbidity and mortalityAnwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 114-120